2011
DOI: 10.1021/jf104992w
|View full text |Cite
|
Sign up to set email alerts
|

Sorption−Desorption of Aminocyclopyrachlor in Selected Brazilian Soils

Abstract: Aminocyclopyrachlor sorption/desorption was investigated in 14 soils from Brazil, representing a range of pH, and organic carbon (OC) and clay contents. The Freundlich equation adequately described behavior of aminocyclopyrachlor in soil. Freundlich sorption coefficient (K(f)) values ranged from 0.06 to 1.64 and 1/n values for ranged from 0.9 to 1.0. Sorption was correlated to OC (K(f,oc) ranged from 11 to 64) and clay contents. The lowest sorption was found for soils with very low OC contents (0.50-0.65%) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 12 publications
3
27
0
3
Order By: Relevance
“…An average aminocyclopyrachlor concentration of 20 mg kg 21 (10% of applied) remained in the top 5 cm across all soil types (Figures 3a and 3b). This is similar to aminocyclopyrachlor desorption observed in 17 different soil types which ranged from sandy to clay textures (Oliveira et al 2011(Oliveira et al , 2013. Approximately 208 mg kg 21 (32% of applied) of quinclorac was retained in the top 5 cm across all soil types (Figures 2a and 2b).…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…An average aminocyclopyrachlor concentration of 20 mg kg 21 (10% of applied) remained in the top 5 cm across all soil types (Figures 3a and 3b). This is similar to aminocyclopyrachlor desorption observed in 17 different soil types which ranged from sandy to clay textures (Oliveira et al 2011(Oliveira et al , 2013. Approximately 208 mg kg 21 (32% of applied) of quinclorac was retained in the top 5 cm across all soil types (Figures 2a and 2b).…”
Section: Resultssupporting
confidence: 72%
“…Aminocyclopyrachlor is more weakly adsorbed to soil surfaces and has a higher leaching potential (Oliveira et al 2011(Oliveira et al , 2013 compared with quinclorac which may have accounted for this difference. Herbicide sorption coefficient (K oc ) values of 446 and 28 for quinclorac and aminocyclopyrachlor, respectively (Hill et al 2000;Shaner 2014a), also support this hypothesis.…”
Section: Resultsmentioning
confidence: 99%
“…Myers & Parker (2011) also noted a long period of residual activity (between three and five months) for species like Eclipta alba, Euphorbia maculata and Senecio vulgaris. Alonso et al (2011) found a positive correlation between the sorption indaziflam and organic carbon content of several Brazilian soils, and classified this herbicide as moderate potential for leaching in the soil profile.…”
Section: Introductionmentioning
confidence: 83%
“…It is used in the US since 2010 to control broadleaf weeds and brushes in non-crops areas such as lawns (residential, industrial, and institutional), golf courses, parks, cemeteries, athletic fields, and sod farms [1] and is currently under development in Brazil for the cultivation of sugarcane and pasture [2,3]. Although limited information is known about aminocyclopyrachlor fate in soil, studies reported that this herbicide is highly water soluble, non-volatile, and can be easily leached in soils due to its low sorption capacity and high desorption capacity [4,5]. Its dissipation in the environment is thus expected to occur predominantly via aqueous photolysis and leaching becoming a potential groundwater contaminant [6].…”
Section: Introductionmentioning
confidence: 99%